Protocol evelopment for fresh - cut fruits and fruit mix preparation - Amith P.K (Department of Processing technology, College of Agriculture, 2012)
The present investigation on “Protocol development for fresh- cut fruits and fruit mix preparation” was carried out at the Department of processing Technology, College of Agriculture, Vellayani, during the period of 2010-2012, with the objective to standardize an efficient and economic protocol for development of fresh- cut fruits and fruit mix with extended shelf life and to study the acceptability of the standardized technology.